The efficacy and safety of varenicline alone versus in combination with nicotine lozenges for smoking cessation among hospitalised smokers (VANISH): study protocol for a randomised, placebo-controlled trial. Issue 10 (6th October 2020) - Gobarani, Rukshar Kaizerali; Abramson, Michael J; Bonevski, Billie; Weeks, Gregory R; Dooley, Michael J; Smith, Brian J; Veale, Antony; Webb, Ashley; Kirsa, Sue; Thomas, Dennis; Miller, Alistair; Gasser, Rudi; et al.
Abstract : Introduction: Smoking is a leading cause of premature deaths globally. The health benefits of smoking cessation are many. However, majority of quit attempts are unsuccessful. One way to potentially improve success rates is to evaluate new combinations of existing smoking cessation therapies that may work synergistically to decrease the intensity of withdrawal symptoms and cravings. Aims: To evaluate the feasibility, efficacy and safety of the combination of varenicline and nicotine replacement therapy (NRT) lozenges versus varenicline alone in assisting hospitalised smokers to quit. Methods and analysis: This is a multicentre, randomised, placebo-controlled trial. Adults with a history of smoking ≥10 cigarettes per day on average in the 4 weeks prior to their hospitalisation will be recruited. Participants will be randomly assigned to either the intervention group and will receive varenicline and NRT lozenges, or the control group and will receive varenicline and placebo lozenges. All participants will be actively referred to behavioural support from telephone Quitline. Participants are followed up at 1 and 3 weeks and 3, 6 and 12 months from the start of treatment. The primary outcome is carbon monoxide validated prolonged abstinence from 2 weeks to 6 months after treatment initiation. Secondary outcomes include self-reported and biochemically validated prolonged and point prevalence abstinence at 3, 6 and 12 months, self-reported adverse events, withdrawal symptoms and cravings, adherence to treatment, Quitline sessions attended and others. According to the Russell Standard, all randomised participants will be accounted for in the primary intention-to-treat analysis. Ethics and dissemination: The trial will be conducted in compliance with the protocol, the principles of Good Clinical Practice, the National Health and Medical Research Council National Statement on Ethical Conduct in Human Research (updated 2015) and the Australian Code for the Responsible Conduct of Research (2018). Approval will be sought from the Human Ethics Committees of all the participating hospitals and the university. Written informed consent will be obtained from each participant at the time of recruitment. Trial registration number: Australia New Zealand Clinical Trials Registry (ACTRN12618001792213).